Conflitti del lavoro, lavoro in conflitto. Trasformazioni aziendali globali e nuove forme di fragilità e precarizzazione - D’Aloisio, Fulvia (EtnoAntropologia, 2016)
The paper focuses on the issue of conflict in contemporary metal-mechanic work and inside the traditional site of blucollars conflict, the factory. Based on an ethnographic research on the Fiat-Sata factory of Melfi (founded in 1993), it shows the progressive change of the line of conflict between workers and owners towards a more subjective and existential conflict between time of work and private and familiar life. As some scholars think, the ‘old fashioned’ conflict has not totally disappeared, rather it has changed its sense and value, flowing towards a different configuration. The work reduction, started in Melfi from 2011, when the factory began the decline of its production and resorting to layoffs, has radically changed the work condition and the perception of the future. The sense of the recruitment in FIAT, for the lucky ones who were hired in 1993 and 1994, was such as an existential turnabout, compared to a very contrary past; more recently, the long period of CIG (Cassa Integrazione Guadagni, from the end of 2011 to 2014), and then the new configuration of the multi-national enterprise FCA, has increased uncertainty, precariousness, fear to loss the job. In this scenario, the conflict should appear as already exceeded, or simply we have to rethink our idea of class conflict, in the current era of manufacturing production, as a new win of the upper classes.